Change Orders and Their Domino Effect: Insights from Public Construction Projects in the Kingdom of Saudi Arabia - Badr T. Alsulami (Buildings)
Public construction projects in Kingdom of Saudi Arabia (KSA), particularly in the Makkah region, are important for the infrastructure and economic growth of the country. However, these projects often face challenges from change orders (COs), which lead to notable cost and schedule overruns. This study examines 32 public construction projects completed between 2010 and 2019 to analyze the impacts of COs on project performance. Results indicated that COs are associated with significant schedule overruns, ranging from 22% to 200%, and cost increases between 2.67% and 42.86%. Approximately 80.65% of the projects experienced cost overruns, with only one project adhering to its original budget. The ANOVA results revealed that differences in cost and schedule overruns based on project size, type, and managing department are not statistically significant. This highlighted that challenges posed by COs are consistent across different project categories and departments, showing systemic inefficiencies rather than project-specific issues. Variability in overruns within certain groups, such as departments, emphasizes the need for further exploration into localized practices and conditions. Finally, the study provides actionable recommendations to mitigate the adverse effects of COs, including standardized protocols for CO management, early stakeholder engagement during planning phases, adoption of advanced monitoring tools such as BIM, and the inclusion of contingency funds aligned with project complexity.